2007
DOI: 10.1007/s00726-007-0544-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of γ-aminobutyric acid by Streptococcus salivarius subsp. thermophilus Y2 under submerged fermentation

Abstract: Gamma-aminobutyric acid (GABA), a major inhibitory neurotransmitter in the central nervous system, has several well-known physiological functions and has been applied to the production of many drugs and functional foods. The technology of GABA production via submerged fermentation by Streptococcus salivarius subsp. thermophilus Y2 was investigated in this paper. It indicated that the GABA production was related to the biochemical characteristics of glutamate decarboxylase (GAD) of S. salivarius subsp. thermoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 12 publications
4
132
3
1
Order By: Relevance
“…paracasei NFRI 7415 isolated from Japanese traditional fermented food funasushi (Komatsuzaki et al, 2005). Recently, Yang et al (2008) has reported to produce 78 mM of GABA using Streptococcus salivarius in China, and domestic researchers are developing the isolation of strains producing GABA and have reported to produce 19 mM, 251 mM of GABA respectively by isolation of GABA-producing strains such as Lb. brevis OPK 3, Lb.…”
Section: Introductionmentioning
confidence: 99%
“…paracasei NFRI 7415 isolated from Japanese traditional fermented food funasushi (Komatsuzaki et al, 2005). Recently, Yang et al (2008) has reported to produce 78 mM of GABA using Streptococcus salivarius in China, and domestic researchers are developing the isolation of strains producing GABA and have reported to produce 19 mM, 251 mM of GABA respectively by isolation of GABA-producing strains such as Lb. brevis OPK 3, Lb.…”
Section: Introductionmentioning
confidence: 99%
“…However, S. salivarius subsp. thermophilus Y2 did not increase GABA production significantly when glutamate was added 10-20 g LG 1 of media, suggesting that these concentrations of glutamate are not appropriate for the synthesis of GABA in this species (Yang et al, 2008).…”
Section: Effect Of Temperaturementioning
confidence: 90%
“…The contents of extracellular GABA accumulated in the culture medium were extracted according to the method of Yang et al (2008) with minor modifications. First, the culture broth was separated from cells by centrifugation (8000×g for 15 min at 4°C) and the supernatant was diluted 50 fold with 7% (v/v) of glacial acetic acid.…”
Section: Gaba Quantificationmentioning
confidence: 99%
See 2 more Smart Citations